Construction of dissection protocols as a learning object for teaching comparative animal anatomy - Passos Pequeno, Andréia (2021)
Introduction: learning objects allow meaningful learning through the use of a dynamic methodology that greatly increases students’ motivation and makes learning anatomy more effective. The purpose of the present study was to develop dissection protocols as a learning object for the teaching of Comparative Anatomy, by students of the Anatomy of Domestic Animals II course of the School of Veterinary Medicine of the Universidad Nacional de Costa Rica..Material and Methods: a total of 25 students in the course participated in the definition of dissection protocols for bovine,equine, canine and feline species, presented as texts accompanied by photographs of dissections, as well as explanatory videos for each of the species and their body regions. At the end of the course participating students participated in a survey with objective questions about the process of constructing learning objects. Results: a total of 6 dissection protocols reported in text and atlas formats were prepared, accompanied by explanatory videos. The 25 students who participated in this teaching experience participated voluntarily in the survey. Conclusion: the definition of dissection protocols as a learning object contributed to a better understanding of theoretical concepts of anatomy and development of manual skills, improving motivation and learning of the subject matter of this discipline.